The Mediation Effect of Service Innovation on the Relationship Between Promotional Strategies and Market Share in Medical Schemes, South Africa - Michael Mncedisi Willie; Abigail Chivandi (Yayasan Aya Sophia Indonesia, 2025)
Orientation: The dynamic global healthcare landscape requires ongoing adaptation and innovation. Service innovation (SI) is pivotal for healthcare funders and providers, particularly in medical schemes, where it significantly enhances the effectiveness of promotional strategies (PS) and improves market share (MS). Research Purpose: This study explores the mediating effect of service innovation on the relationship between promotional strategies and market share in the private healthcare sector, focusing on medical scheme beneficiaries in Gauteng, South Africa. It aims to assess how SI amplifies the impact of PS on MS and the implications of outsourcing marketing services. Motivation for the Study: Rising complexity in the healthcare market and the need for medical schemes to attract and retain members amid growing competition drive this study. Understanding how service innovation mediates the relationship between promotional strategies and market share offers insights into optimising marketing efforts for better market penetration. Research Approach/Design and Method: A quantitative cross-sectional design was employed, using snowball sampling to gather data from 260 beneficiaries in Gauteng. Baron and Kenny's mediation framework was used for analysis, with validation through STATA software and Zhao, Lynch, and Chen's approach. Main Findings: Service innovation partially mediates the relationship between promotional strategies and market share, with approximately 12% of the impact being mediated by SI, highlighting its role in enhancing promotional effectiveness. Practical/Managerial Implications: Integrating service innovation into promotional strategies is crucial for healthcare funders and providers to improve market share. The study also underscores the importance of aligning outsourced marketing services with organisational goals to maximise effectiveness. Contribution/Value-Add: This research provides empirical evidence on the partial mediation effect of service innovation, offering valuable insights for optimising marketing strategies and addressing challenges in outsourcing marketing services. Thus, it enhances competitive positioning in the healthcare sector.